Exploratory Study of Customer Delight in Music Festival: A Case Study of Focal Point 2015 - Sinatrya, Kevin Putra; Iskandar, Budi Permadi (Journal of Business and Management, 2016)
Abstract. The number music festival in Bandung has increase rapidly in recent years and the competition that tighter than before. In accordance with growth of music festival in Indonesia and Bandung both in numbers and creation, it is not enough for creating event that made the visitor felt satisfied, they have to be delighted. Having a delighted customer will leads into higher loyalty level of customer more than satisfied customer. Hence, this research is intended to analyzing the journey of customer delight formation and took a case of Focal Point 2015. Focal Point is a bi-annual thematic music festival that took picnic as the theme that has ambition to grow in the future. Hence, it is not enough to create an event that make visitors feel satisfied, they have to be delighted. To know the journey of customer delight in Focal Point 2015, author combining several concept of customer delight into a conceptual framework for measuring customer journey since there is no exact variables in measuring customer delight. The variables are consists of surprisingly positive performance, positive affection, level of satisfaction, and customer delight. Qualitative research is applied for this research in order for knowing deeper of what visitors really think and feel towards experience given by Focal Point 2015. Purposive case is used to map out the surprise elements that triggering customer delight on each person and conclude it based on the saturated pattern of data. Fifteen respondents were interviews for generating the customer delight journey. Positive surprise elements are found as the catalyst to delighted customer. Of the entire positive surprise element, atmosphere and picnic activity as Focal Point 2015 theme were indicating as the most memorable when visitor recalled the moments. The result of this study confirms that visitors of Focal Point 2015 were delighted towards all the experience perceived from the event. Â Keywords: Consumer Behavior, Customer Delight, Surprise Elements, Music Festival, Utilitarian and Hedonic Consumption